Yield, energy and economic analysis of organic guava (Psidium guajava) production under various organic farming treatments - RAM, R A; VERMA, A K (The Indian Journal of Agricultural Sciences, 2017)
Agrochemicals based horticulture production system is neither sustainable nor eco-friendly. Cost effective organic production of horticultural crops is the need of the day to provide safe food to the consumers. In this regard, a field experiment was carried out in randomized block design with 3 replications on 18 years old trees of guava cv Allahabad Safeda in 2014 and 2015 at ICAR- Central Institute for Subtropical Horticulture, Lucknow, India (26.9044° N, 80.7654° E). Seven organic farming treatments were selected as treatments, viz. T1, T2, T3, T4, T5, T6 and T7 for the study. Results indicated that T3 achieved maximum energy ratio (10.42±0.14), minimum specific energy (221.24±2.60 MJ/T) and maximum energy productivity (4.53±0.06 kg/MJ). Economic analysis of the production also indicated that that T3 achieved minimum input cost (825.87±9.70 `/T) and resulted into maximum cost benefit ratio (12.14±0.16). Based on the study it is concluded that T3 was energy efficient and profitable practice among other organic farming practices.